Hepatic Overexpression of GRP94 in a Rabbit Model of Parenteral Nutrition-Associated Liver Disease - Xueping Zhu; Xiaomin Zhang; Lingling Yu; Yumin Xu; Xing Feng; Jian Wang (Gastroenterology Research and Practice)
Objective. To use a rabbit model of parenteral nutrition-associated liver disease (PNALD) to study changes of the endoplasmic reticulum stress (ERS) marker glucose regulatory protein 94 (GRP94) and determine its role in the pathogenesis of PNALD. Methods. A rabbit PNALD model total parenteral nutrition (TPN) group was established. A corresponding control group received breast-feeding for one week. Serum biochemical parameters were measured and liver histological examinations were performed. The level of GRP94 mRNA and protein were measured. Results. The results showed that the serum TBIL, DBIL, and γ-GT levels in the TPN group were significantly higher than those in the control group, while levels of serum ALB in TPN group were significantly lower than those in the control group. The immunohistochemistry results showed that the protein expression level of GRP94 in the liver of TPN group was significantly increased compared with the control group. The RT-PCR results showed that the level of GRP94 mRNA in the liver of the TPN group was significantly higher compared with the control group. Conclusions. The mRNA and protein levels of GRP94 in the TPN group were both significantly increased, indicating that ERS may be directly related to the occurrence and development of PNALD.